2019
DOI: 10.1111/iej.13183
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous emphysema in patients undergoing root canal treatment: a systematic review of the factors affecting its development and management

Abstract: Background Subcutaneous emphysema is an infrequent mishap during root canal treatment which, in rare cases, can lead to severe complications. Aim To systematically review the literature on the factors affecting the development of subcutaneous emphysema during root canal treatment, and on its management. Data sources An electronic search was conducted in EMBASE (1947–2018), LILACS (1982–2018), PubMed (1950–2018), SciELO (1997–2018), Scopus (1970–2018), Web of Science (1900–2018) and two grey literature database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
(152 reference statements)
1
6
0
Order By: Relevance
“…As stated by the valuable paper by Fasoulas et al [21], SCE is more frequent in females than in males, with a ratio of 2:1, this was also confirmed in our database. In most of the articles cited in this review, the endodontic procedure which leads to soft tissue swelling is initial RCT (78%), while 14% happens during non-surgical RCT and 5% is linked to endodontic surgery [22] Lastly, 3% arises throughout the surgical management of acute apical abscesses [15].…”
Section: Discussionsupporting
confidence: 91%
“…As stated by the valuable paper by Fasoulas et al [21], SCE is more frequent in females than in males, with a ratio of 2:1, this was also confirmed in our database. In most of the articles cited in this review, the endodontic procedure which leads to soft tissue swelling is initial RCT (78%), while 14% happens during non-surgical RCT and 5% is linked to endodontic surgery [22] Lastly, 3% arises throughout the surgical management of acute apical abscesses [15].…”
Section: Discussionsupporting
confidence: 91%
“…As stated by Fasoulas et al [ 13 ], subcutaneous emphysema is almost twice as common in females than males. In their systematic review, emphysema was mainly reported in females (39/65) rather than males (20/65) and the age of the patients ranged from 18 to 63 years (mean = 38 years).…”
Section: Discussionmentioning
confidence: 95%
“…Several complications resulting from H 2 O 2 use have been reported in dentistry, where high‐pressure systems can introduce H 2 O 2 into small enclosed spaces. A systematic review pertaining to subcutaneous emphysema in patients undergoing root canal treatment linked “air under pressure” systems, such as air‐water sprays, to the introduction of H 2 O 2 through the apical foramen 3 . The majority of these cases reported subcutaneous emphysema as the complication; however, there were rare cases of air dissecting into deeper fascial planes leading to pneumomediastinum and air embolism.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of case reports in the dental, general surgery, and orthopedic literature have linked H 2 O 2 irrigation with the development of subcutaneous emphysema, air embolism, or pneumomediastinum. 3 Here we present the case of a 22-month-old patient who experienced massive subcutaneous emphysema, pneumo-orbit, and pneumomediastinum after irrigation of a penetrating neck injury from a meat thermometer with H 2 O 2.…”
Section: Introductionmentioning
confidence: 99%